2010
DOI: 10.1039/c0ee00139b
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube architectures as catalyst supports for proton exchange membrane fuel cells

Abstract: Catalyst support materials exhibit great influence on the performance and durability of proton exchange membrane (PEM) fuel cells. This minireview article summarises recent developments into carbon nanotubebased support materials for PEM fuel cells, including the membrane electrode assembly (MEA). The advantages of using CNTs to promote catalyst performance and stability, a perspective on research directions and strategies to improve fuel cell performance and durability are discussed. It is hoped that this min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
135
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(137 citation statements)
references
References 82 publications
0
135
0
2
Order By: Relevance
“…Along with the development of nanocarbon science, more and more novel nanostructured carbon materials have been adopted as new support materials, and have already shown much better loading effect because of their unique nanostructure. [3][4][5][6][7] Among the reported nanocarbon supports, ordered mesoporous carbons (OMCs) are especially impressive, and are attracting increasing scientific interests due to their unusual physical and chemical characteristics, such as ordered and tailored nanostructure, high surface area, large pore volume, narrow pore size distribution in the mesopore range, high controlled pore surface chemistry, good electrical conductivity and so on. [5][6][7][8][9][10][11] Joo et al have firstly reported that an OMC with a highly ordered hexagonal array of nanoporous carbons, CMK-5, supported a high dispersion of Pt nanoparticles (<3 nm), exceeding that of many common microporous carbon materials, which gave rise to a promising electrocatalytic activity for oxygen reduction reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the development of nanocarbon science, more and more novel nanostructured carbon materials have been adopted as new support materials, and have already shown much better loading effect because of their unique nanostructure. [3][4][5][6][7] Among the reported nanocarbon supports, ordered mesoporous carbons (OMCs) are especially impressive, and are attracting increasing scientific interests due to their unusual physical and chemical characteristics, such as ordered and tailored nanostructure, high surface area, large pore volume, narrow pore size distribution in the mesopore range, high controlled pore surface chemistry, good electrical conductivity and so on. [5][6][7][8][9][10][11] Joo et al have firstly reported that an OMC with a highly ordered hexagonal array of nanoporous carbons, CMK-5, supported a high dispersion of Pt nanoparticles (<3 nm), exceeding that of many common microporous carbon materials, which gave rise to a promising electrocatalytic activity for oxygen reduction reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Pt/C) have been considered as the most effective elecrocatalysts for ORR in PEM fuel cells due to their high activities and good stabilities. [1][2][3][4][5][6][7][8][9] However, the issues of high cost, scarce sources and long-term durability limit their large-scale production and hinder the commercialization of PEM fuel cells. [10][11][12][13][14] In order to decrease the cost of electrocatalysts and eliminate their dependence on noble metals, various non-noble metal catalysts have been explored recently as alternatives to the Pt-based electrocatalysts, which include chalcogenide catalysts, [15][16][17][18][19] transition metal macrocyclic compounds, [20][21][22] transition metallic oxides [23][24][25][26][27] and carbon-based catalysts.…”
mentioning
confidence: 99%
“…7,8 Recently, the authors have reported on the generation of a range of high electrochemically active surface area carbon electrodes suitable for use in a variety of electrochemical devices. 9 In spite of the established high porosity and available surface area of these structures, the measured electrochemical capacitance is generally quite low (ca. 45-150 F g À1 ).…”
Section: 2mentioning
confidence: 99%
“…9,11,16,17,19 To date, this dependence on CNT soot as the starting material is one of the most significant impediments to the generation of viable microwave-synthesised mNP/CNT electrodes. The problematic processability of CNT soot into a finite number of structures is well documented, and, in addition, a large proportion of the metallic nanoparticles remain unavailable to the electrolyte after processing due to pore filling effects.…”
mentioning
confidence: 99%